Studi Pemaknaan Ibu Rumah Tangga Tentang Tindak Kekerasan Seksual Desa Kwanyar Kabupaten Bangkalan - Sri Hidayati; Achmad Syarifudin (Journal of Social, Culture, and Language, 2024)
Sexual Violence is any act of degrading, insulting, harassing, or attacking a person's body, or reproductive function, due to imbalances in power relations and gender. This study aims to provide understanding and interpretation to the community related to sexual and family violence both committed on children and married couples. Research techniques using action research, research not only always looks for data, but also conducts socialization and counseling about the Sexual Violence Criminal Law both about sanctions for perpetrators and protection rights for victims. The results showed that this externalization was influenced by the strong patriarchal culture so that women were not equal to their husbands. Objectification is in the form of rationalization of actions committed to her husband related to sexual relations as a necessity and obligation carried out by the wife to the husband. Internalization is the implication of inequality between husband and wife in the household, this makes the wife rationalize a number of reasons for continuing to carry out her role as wife. Lack of public understanding of sexual violence in the form of mapping forms of sexual violence cases in the family both in children and married couples such as physical violence, verbal violence, psychological violence, economic violence and counseling in the form of direct socialization and FGD. As an effort to prevent and protect, education is carried out through social media for perpetrators and protection for victims.Keywords: Study, Meaning, Sexual Violence, Domestic